Proxy Pembiayaan Green Financing pada Bank Umum Syariah terhadap Energi Terbarukan (2005-2024) - Meylani, Raisha Alya Meylani; cupian, Cupian; Noven, Sarah Annisa (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the development of green financing proxied by financing in the sector of electricity, gas, and water at Islamic Commercial Banks in Indonesia during the period 2005-2024. Using a descriptive-quantitative approach and secondary data, the analysis focuses on trends, proportional allocation, and changes in financing patterns within the framework of sustainable finance policies. The findings indicate that financing in the proxy sectors has increased gradually, although its proportion to total Islamic Commercial Bank financing remains relatively limited. The implementation of sustainable finance policies, including the Roadmap for Sustainable Finance, POJK No. 51/POJK.03/2017, and the Indonesian Green Taxonomy, is associated with a more consistent allocation of financing, albeit through a gradual adjustment process. In parallel, the development of renewable energy in Indonesia has progressed more steadily than the growth of Islamic bank financing in the proxy sectors. From an Islamic economics perspective, these findings reflect a significant internalization of maqāṣid al-sharī’ah, particularly hifz al-bi’ah, within the financing practices of Islamic Commercial Banks.